Stratigraphic architectural development and growth history of a Paleocene isolated carbonate platform, north-central Sirte Basin, Libya: Interplay of tectonics and eustasy - Muneer Abdalla; Abdalla Abdelnabi; Ahmad Issa; Meeloud Abdullah; Husamaldeen Zubi; Yousf Abushalah (Results in Earth Sciences)
Isolated carbonate platforms are present throughout the geologic record and often serve as important hydrocarbon reservoirs. Example of these isolated platforms include the Great Bahamas Bank, Great Bank of Guizhou, Yucatán, and Queensland Plateau. In this study, 3D seismic and wireline logs are utilized to unravel the internal stratigraphic architecture, evolutionary history, and major controls on the development and eventual demise of a Paleocene-age isolated platform within the RG Field in north-central Sirte Basin, north-central Libya. Five distinct seismic facies reveal diverse lithologies and depositional settings. Four key depositional settings are identified from the seismic facies and attributes: the platform interior (lagoon) with pinnacles, reef margin, slope, and intraplatform seaway. The studied platform that has a lateral extent of at least 350 km² comprises four stratigraphic sequences separated by unconformable sequence boundaries deciphered from seismic and well log data. The growth of the platform began at the start of the Paleocene with patch reefs developing on pre-existing Cretaceous horst and ceased at the end of the Paleocene due to subaerial exposure. The evolution of the platform occurred as vertical aggradation within the platform interior, margins, the intraplatform seaway, and as progradation on the slopes. Tectonic subsidence resulting from the basin rifting at the late stages of the Cretaceous along with repeated rising sea-level changes, provided the space for carbonate platform growth. The Cretaceous horst structure created a shallow-water positive feature that encouraged sediment accumulation. Short-term sea-level changes further influenced internal stratigraphic complexity and sequence development, detectable as cycles of third-order magnitude in the seismic data. Findings from this research offer valuable insights into isolated platform formations in extensional rift settings, aiding the prediction of depositional settings and sedimentary facies that could possibly host hydrocarbon reservoirs. The created model can also be a useful reference for other carbonate platforms worldwide.